Binary mesovortex structure associated with southwest vortex. (12th May 2017) - Zhou, Kuo; Liu, Haiwen; Zhao, Liang; Zhu, Yuxiang; Lin, Yihua; Zhang, Fuying; Fu, Ning
Abstract: Previous work has concluded that the southwest vortex (SWV) is a single mesoscale vortex. Applying the National Centers for Environmental Prediction Final Operational Global Analysis, the Interim European Centre for Medium‐Range Weather Forecasts Re‐Analysis, and the non‐hydrostatic mesoscale Advanced Research Weather Research and Forecasting (WRF) model to a case study, we discovered a new type of SWV associated with another coexisting mesoscale warm and moist vortex. In the case study, meso‐β‐scale vortex‐A was generated at 1800 UTC 17 July, and dissipated around 0500 UTC 18 July 2013, with a lifespan of approximately 11 h. Vortex‐B occurred at 0600 UTC 17 July and moved out of the Sichuan Basin at 0800 UTC 18 July 2013, remaining over the basin for approximately 26 h. Stronger atmospheric upward motion and two mesoscale rainbelts associated with each of the vortices further demonstrate the binary mesoscale vortex structure related to the SWV using the WRF model. The quasi‐geostrophic balance of the two mesoscale cyclonic circulations is responsible for the generation and maintenance of the two closed mesoscale vortices. Abstract : Synoptic conditions of 700‐hPa geopotential heights (blue contours, units: gpm) and flow field analyzed from FNL data at (a) 1200UTC 17 July, (b) 1800UTC 17 July, (c) 0000UTC 18 July, and (d) 0600UTC 18 July 2013. Shading shows the terrain of Sichuan Basin (units: m) and the value of 3080 gpm in black contour is used to highlight the binary vortex structure. The symbols 'A' and 'B' in panels (b) and (c) denote centers of the binary vortices, respectively.